Tindak Tutur Ekspresif Memuji Pada Kolom Komentar Postingan Tiktok @Amuhaiminiskandar - Fajriani Fitri (Universitas Palangka Raya, 2025)
. This study examines expressive speech acts of praising in the comment sections of TikTok posts on the @amuhaiminiskandar account. The research aims to analyze the forms, functions, and contexts of praising speech acts based on the speech act theory proposed by John Searle. This study employs a qualitative descriptive method with a documentation technique, where data are collected from comments on TikTok posts of the @amuhaiminiskandar account. The findings reveal that praising speech acts reflect various expressions of appreciation toward the content, the public image of Cak Imin, and his political attitudes and style. This research contributes to understanding the dynamics of digital communication through social media, particularly TikTok, as one of the most widely used platforms in Indonesia.